PERANCANGAN ALAT PENGATUR KELEMBAPAN OTOMATIS PADA MESIN HATCHER TELUR BEBEK DENGAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Septian, Ilham Dwi; Satoto, Handy Febri (Universitas Majalengka, 2024)
The duck farming business is an activity where farmers process ducks to breed and maintain them to obtain benefits and results from this activity. Ducks are quite popular among various groups, from small children to the elderly. UMKM in the Jombang area are located on Jl. Gatot Subroto No. 29A Mojongapit, Jombang. These UMKM are KUB chicken farms and broiler duck hatcheries. Hatching of broiler ducks is carried out using an automatic hatching machine that can turn the eggs automatically. The UMKM hatching machine processes 500 eggs each period. If the temperature and humidity method is not checked periodically, the egg hatching yield will be 75%. If you want to increase the hatching presentation, you can check regularly to reach 80%, but this takes too much time and energy. Therefore, I will make a tool that can regulate the humidity of the incubator. In solving this problem, the QFD method is used to fulfill consumer desires in making tools. Using the QFD method will make the tool making more optimal because before the tool is made a survey is carried out to determine consumer interest. The results of this research are tool designs that are made according to consumer interests.